Lignocellulose biomass bioconversion during composting: Mechanism of action of lignocellulase, pretreatment methods and future perspectives. (January 2022) - Wu, Di; Wei, Zimin; Mohamed, Taha Ahmed; Zheng, Guangren; Qu, Fengting; Wang, Feng; Zhao, Yue; Song, Caihong
Abstract: Composting is a biodegradation and transformation process that converts lignocellulosic biomass into value-added products, such as humic substances (HSs). However, the recalcitrant nature of lignocellulose hinders the utilization of cellulose and hemicellulose, decreasing the bioconversion efficiency of lignocellulose. Pretreatment is an essential step to disrupt the structure of lignocellulosic biomass. Many pretreatment methods for composting may cause microbial inactivation and death. Thus, the pretreatment methods suitable for composting can promote the degradation and transformation of lignocellulosic biomass. Therefore, this review summarizes the pretreatment methods suitable for composting. Microbial consortium pretreatment, Fenton pretreatment and surfactant-assisted pretreatment for composting may improve the bioconversion process. Microbial consortium pretreatment is a cost-effective pretreatment method to enhance HSs yields during composting. On the other hand, the efficiency of enzyme production during composting is very important for the degradation of lignocellulose, whose action mechanism is unknown. Therefore, this review describes the mechanism of action of lignocellulase, the predominant microbes producing lignocellulase and their related genes. Finally, optimizing pretreatment conditions and increasing enzymatic hydrolysis to improve the quality of composts by controlling suitable microenvironmental factors and core target microbial activities as a research focus in the bioconversion of lignocellulose during composting in the future. Highlights: The pretreatment destroys the structure of refractory lignocellulose. Combined pretreatment and composting have a synergistic effect on HSs formation. The key roles of lignocellulase during composting have been confirmed. Directional control HSs formation has been proposed.